(3agQSJ eDdaGJ GdSjhWis - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hcai hSdGe Ydi YHGOg GdPjf EUWai hHYO agPg agQSg eDdaGJ GdSjhWi GdTGaYi bGd QMeg Gddg JYGdi gPg agQSJ eDdaGJi eQJHkG Ydi Gdafhf af GdJaSjQ hJYdjbGJ GdbQBf s
(3BNQgG (B:s
(3JHjV GdUMjaI HefGbH GdEeGe CHj MfjaI GdeeGdc HefGbH GdEeGe eGdc QVi Gddg Yfge CLeYjf Je cJGH GdagQSI HMeO Gddg hYhfg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3fSNI ecQQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3agGQS hecJHGJs